A new method for dating impact events – Thermal dependency on nanoscale Pb mobility in monazite shock twins. (1st December 2021) - Fougerouse, Denis; Cavosie, Aaron J.; Erickson, Timmons; Reddy, Steven M.; Cox, Morgan A.; Saxey, David W.; Rickard, William D.A.; Wingate, Michael T.D.
Abstract: To test the potential of deformation twins to record the age of impact events, micrometre-scale size mechanical twins in shocked monazite grains from three impact structures were analyzed by atom probe tomography (APT). Shocked monazite from Vredefort (South Africa; ∼300 km crater diameter), Araguainha (Brazil; ∼40 km diameter), and Woodleigh (Australia; 60 to 120 km diameter) were studied, all from rocks which experienced pressures of ∼30 GPa or higher, but each with a different post-impact thermal history. The Vredefort sample is a thermally recrystallised foliated felsic gneiss and the Araguainha sample is an impact melt-bearing bedrock. Both Vredefort and Araguainha samples record temperatures > 900 °C, whereas the Woodleigh sample is a paragneiss that experienced lower temperature conditions (350–500 °C). A combined 208 Pb/ 232 Th age for common {1 2 ¯ 2 ¯ } twins and shock-specific ( 1 ¯ 01) twins in Vredefort monazite was defined at 1979 ± 150 Ma, consistent with the accepted impact age of ∼2020 Ma. Irrational η1 [ 1 ¯ 1 ¯ 0] shock-specific twins in Araguainha monazite yielded a 260 ± 48 Ma age, also consistent with the accepted 250–260 Ma impact age. However, the age of a common (001) twin in Araguainha monazite is 510 ± 87 Ma, the pre-impact age of igneous crystallisation. These results are explained by the occurrence of common (001) twins in tectonic deformation settings, in contrast to the ( 1 ¯ 01) and irrational η1 [ 1 ¯ 1 ¯ 0] twins, which have only been documented in shock-deformed rocks. In Woodleigh monazite, APT age data for all monazite twins [(001), ( 1 ¯ 01), newly identified 102°/< 4 ¯ 23> twin], and host monazite are within uncertainty at 1048 ± 91 Ma, which is interpreted as a pre-impact age of regional metamorphism. We therefore are able to further constrain the poorly known age of the Woodleigh impact to <1048 ± 91 Ma. These results provide evidence that Pb is expelled from monazite during shock twin formation at high temperature (Vredefort and Araguainha), and also that Pb is not mobilised during twinning at lower temperature (Woodleigh). Our study suggests that twins formed during shock metamorphism have the potential to record the age of the impact event in target rocks that are sufficiently heated during the cratering process.